El texto del Bellum Gallicum de César en los códices de la clase β conservados en España: contribuciones a la historia de la tradición textual - García Villena, Ana José (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
Philological analysis of Caesar’s Bellum Gallicum transmitted by the six manuscripts of the b-class preserved in the Spanish libraries, in order to clarify its relationship with the textual tradition. They are these codices: El Escorial, N.III.22; Granada, BU Caja B-17; Madrid, BN Ms 10054, BN Ms 12867 and BN Ms Res 242; Valencia, BU Ms 396; they are all of Italian origin and were written in the fifteenth century. The examination of the paratextual elements (tituli and colophons) and the textual variants allows to distinguish between two kinds of readings: on the one hand, the conjunctive variants with the old textual tradition, that show the connection with the manuscripts of the a-class, and particularly with B, the oldest witness of Bellum Gallicum; on the other hand, the separative errors of these manuscripts, unknown unti now, that prove their origin from a common hyparchetype, closely connected with the codex Leidensis Vossianus F 90 (s XIV c.). All this allows us to reconstruct the history of this branch of the tradition. We also analyse the separative errors, in order to establish their critical value; these significative readings are shared by other recentiores and the old editions of Bellum Gallicum.